Pandangan Ulama dan Praktisi Hukum terhadap Validitas Tes DNA dalam Penyelesaian Sengketa Waris - Ahmad Alamuddin Yasin (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren, 2025)
This study aims to explore scholars’ perceptions regarding the validity of DNA testing in resolving inheritance disputes from the perspective of Islamic law. The research involves scholars from two groups: the Indonesian Council of Ulama (MUI) and pesantren-based scholars. It employs a qualitative descriptive method, using primary data collected through in-depth interviews and secondary data from legal documents and relevant literature. The data were analyzed through processes of data reduction, presentation of findings, and conclusion drawing. The results indicate that the use of DNA testing in inheritance disputes is a complex issue that requires caution. Although recognized as a scientifically valid and accurate form of evidence, DNA tests cannot serve as the sole basis for legal decisions. They must be viewed as part of an overall body of evidence and integrated with Sharia principles that prioritize justice, public benefit, and the preservation of family dignity. Scholars from MUI and KH. Ahmad Rifqi Chowas from the pesantren community stress that while technologies like DNA testing offer high accuracy in determining biological relationships, their use must be prudent and aligned with Sharia principles. In conclusion, DNA testing has significant potential as a supporting tool in resolving inheritance disputes, but its application must be carried out with great care. Religious courts and policymakers need to develop clear guidelines on when and how DNA testing may be used, ensuring that its integration is consistent with Sharia values and does not lead to injustice or social discord.